2023
DOI: 10.15252/embj.2022110620
|View full text |Cite
|
Sign up to set email alerts
|

IDH2 stabilizes HIF‐1α‐induced metabolic reprogramming and promotes chemoresistance in urothelial cancer

Abstract: Drug resistance contributes to poor therapeutic response in urothelial carcinoma (UC). Metabolomic analysis suggested metabolic reprogramming in gemcitabine-resistant urothelial carcinoma cells, whereby increased aerobic glycolysis and metabolic stimulation of the pentose phosphate pathway (PPP) promoted pyrimidine biosynthesis to increase the production of the gemcitabine competitor deoxycytidine triphosphate (dCTP) that diminishes its therapeutic effect. Furthermore, we observed that gain-of-function of isoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 68 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…P53 promoted glutamine metabolism in tumour cells through upregulating GLS2 46 . HIF‐1α inhibition reduced glutamine consumption in tumour cells 47 . Accordingly, tumour characterised by high‐GMPI can be regarded as a representative of high malignancy, which provides additional insights into the function mechanisms of GMPI in OC, and combined therapies targeting GM and oncogenic pathways are expected to be a promising treatment strategy for OC.…”
Section: Discussionmentioning
confidence: 99%
“…P53 promoted glutamine metabolism in tumour cells through upregulating GLS2 46 . HIF‐1α inhibition reduced glutamine consumption in tumour cells 47 . Accordingly, tumour characterised by high‐GMPI can be regarded as a representative of high malignancy, which provides additional insights into the function mechanisms of GMPI in OC, and combined therapies targeting GM and oncogenic pathways are expected to be a promising treatment strategy for OC.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic condition upregulates several proteins including HIF-1α that it is important for adaptation of tumor, including UBC, in hypoxic condition. Angiogenesis or neovascularization is the end point of this adaptation (3,4,6), Hypoxia is also the culprit of treatment resistance in many cancers (8,10) and HIF-1α is one of the underlying etiologies (11)(12)(13). Binding of HIF-1α with its receptor in the nucleus promotes cell proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…21 The accumulation of HIF-1α and the activation of HIF-1αmediated glucose transporters and rate-limiting enzymes in glucose metabolism reduce the efficiency of OXPHOS and promote glycolysis. [22][23][24] Although it has been reported that transcriptional activation of HIF-1α leads to cancer metabolic reprogramming and therapeutic resistance, 25 how lncRNAs regulate HIF-1α activation in ESCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%